2018
DOI: 10.1021/acschembio.8b00414
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling of Protein O-GlcNAcylation Sites by an Isotope-Tagged Cleavable Linker

Abstract: Large-scale quantification of protein O-linked β- N-acetylglucosamine (O-GlcNAc) modification in a site-specific manner remains a key challenge in studying O-GlcNAc biology. Herein, we developed an isotope-tagged cleavable linker (isoTCL) strategy, which enabled isotopic labeling of O-GlcNAc through bioorthogonal conjugation of affinity tags. We demonstrated the application of the isoTCL in mapping and quantification of O-GlcNAcylation sites in HeLa cells. Furthermore, we investigated the O-GlcNAcylation sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 52 publications
(81 reference statements)
1
87
0
Order By: Relevance
“…Consistent with the high levels of modification we observed in our pulldown, recent proteomics experiments using the same chemoenzymatic strategy have identified many different endogenous MYPT1 O-GlcNAcylation sites [42][43][44] localized around two different regions of the protein (Figure 5d). The most N-terminal of these areas, with modification at Ser379 and Thr381, is located near the portion of MYPT1 responsible for binding the phosphatase catalytic subunit PP1cδ and its substrate, phosphorylated MLC [45][46][47] .…”
Section: Mypt1 Is a Heavily And Dynamically O-glcnacylated Proteinsupporting
confidence: 89%
“…Consistent with the high levels of modification we observed in our pulldown, recent proteomics experiments using the same chemoenzymatic strategy have identified many different endogenous MYPT1 O-GlcNAcylation sites [42][43][44] localized around two different regions of the protein (Figure 5d). The most N-terminal of these areas, with modification at Ser379 and Thr381, is located near the portion of MYPT1 responsible for binding the phosphatase catalytic subunit PP1cδ and its substrate, phosphorylated MLC [45][46][47] .…”
Section: Mypt1 Is a Heavily And Dynamically O-glcnacylated Proteinsupporting
confidence: 89%
“…Previous reports suggested that streptavidin-biotin enrichment conducted after proteolysis could result in a higher number of identifications than enrichment conducted prior to protein digestion [30][31][32] . We therefore decided to perform two enrichment approaches in parallel to understand how either method would affect the total number of identifications.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of metabolic labeling and click chemistry has emerged as a powerful method to study proteins and protein modifications (Mahal et al, ; Hang et al, ; Bond and Kohler, ; Dieterich et al, ; Hanson et al, ; Hong et al, ; Smeekens et al, ; Chen et al, ; Cheng et al, ; Spiciarich et al, ; Xiao and Wu, ; Xiao et al, ). Metabolic labeling of glycans with unnatural sugar analogs is an excellent way to study glycans and protein glycosylation (Kayser et al, ; Saxon and Bertozzi, ; Feng et al, ; Aguilar et al, , ; Park et al, ; Qin et al, ). In the recent two decades, the Bertozzi group has performed pioneering work on using unnatural sugar analogs to label glycoproteins (Mahal et al, ; Saxon and Bertozzi, ; Hang et al, ; Breidenbach et al, ).…”
Section: Global Analysis Of Glycoproteinsmentioning
confidence: 99%